Management of Systemic Anti-psoriatic Drugs in Psoriasis Patients with Concurrent Paraplegia or Tetraplegia: Insights From a 6-Year Multicenter, Retrospective Observational Study - Giovanni Damiani; Alessia Pacifico; Stefano Ricciardi; Valeria Corazza; David Trigos; Marco Fiore; Claudio Guarneri (Dermatology and Therapy)
Abstract Introduction Patients with psoriasis (PsO) and permanent spinal cord injuries (SCI) resulting in paraplegia and tetraplegia may experience a higher rate of infections compared to patients with PsO without SCI. It can result in further challenges for therapeutic management with immunosuppressants (biological and non-biological treatments). Thus,  we aimed to evaluate the rate of infections in patients with PsO and SCI treated with systemic immunosuppressants. Methods This multicenter, retrospective observational study enrolled patients with PsO and traumatic SCI undergoing systemic immunosuppressive treatments for at least 5 years. All patients were evaluated by experienced, board-certified dermatologists and neurologists. Demographic and clinical data were collected. Results We enrolled 23 patients with SCI (16 with paraplegia and 7 with tetraplegia) treated with methotrexate (MTX) and different biologics (tumor necrosis factor (TNF) inhibitors (i) and interleukin (IL)-17i/IL-23i). Globally, patients with SCI treated with MTX displayed higher rates of infection compared to those treated with biologics. Patients with paraplegia had lower rates of infection compared to patients with tetraplegia during anti-psoriatic therapies (p < 0.05). Those treated with TNFi had greater rates of infection than those treated with IL-17i/IL-23i (p < 0.001). Patients with psoriatic arthritis (PsA) experienced a significant diagnostic delay and clinical monitoring of PsA severity was challenging. Conclusion In patients with moderate-to-severe PsO and concurrent traumatic SCI, dermatologists should consider using IL-17i/IL-23i as first-line therapy.